HOW LEXICAL DENSITY REVEALS STUDENTS’ ABILITY IN WRITING ACADEMIC TEXT - Syarif, Hermawati; Putri, Rahmi Eka (Lingua Didaktika: Jurnal Bahasa dan Pembelajaran Bahasa, 2018)
Through the analysis of lexical density, students’ progress in language learning, especially in writing can be identified. This article aimed to find out lexical density of students’ writing and to explain how  lexical density shows their ability in writing an academic text. The data were taken from the introduction section of thesis proposals written by English graduate students, with the readers of higher education level. By statistical and descriptive analysis, the study reveals that the lexical density of students’ writing is categorized as less dense (51.19%). Grammatical complexity became the major factor that contributed to lexical density. It was revealed that the complexities emerged since students still have limited knowledge about the language use in writing an academic text. The fact shows that students’ ability in writing  academic text is still in average level. This implies that the ones who write the text should consider the high density for the academic text. It is recommended to provide the topic of lexical density in the subject of academic writing subject in the syllabus of English study program of higher education.